eCM 2008
DOI: 10.22203/ecm.v015a01
|View full text |Cite
|
Sign up to set email alerts
|

A low percentage of autologous serum can replace bovine serum to engineer human nasal cartilage

Abstract: For the generation of cell-based therapeutic products, it would be preferable to avoid the use of animal-derived components. Our study thus aimed at investigating the possibility to replace foetal bovine serum (FBS) with autologous serum (AS) for the engineering of cartilage grafts using expanded human nasal chondrocytes (HNC). HNC isolated from 7 donors were expanded in medium containing 10% FBS or AS at different concentrations (2%, 5% and 10%) and cultured in pellets using serum-free medium or in Hyaff ® -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…In this respect, the presented data, strengthen the interest toward chondrocytes from the nasal septum, which show superior and more reproducible chondrogenic capacity, compared with chondrocytes from articular cartilage (Kafienah et al, 2002; Rotter et al, 2002; Wolf et al, 2008; Mumme et al, 2016). The comparison with articular chondrocytes demonstrated that nasal chondrocytes were able to support the production of a cartilage matrix with adequate functional and biomechanical characteristics both in vitro and in vivo (do Amaral et al, 2012; Pleumeekers et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this respect, the presented data, strengthen the interest toward chondrocytes from the nasal septum, which show superior and more reproducible chondrogenic capacity, compared with chondrocytes from articular cartilage (Kafienah et al, 2002; Rotter et al, 2002; Wolf et al, 2008; Mumme et al, 2016). The comparison with articular chondrocytes demonstrated that nasal chondrocytes were able to support the production of a cartilage matrix with adequate functional and biomechanical characteristics both in vitro and in vivo (do Amaral et al, 2012; Pleumeekers et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Chondrocytes derived from the nasal septum are highly promising cell source for the repair of articular cartilage defects since a great capacity to generate hyaline-like cartilage tissues, with the plasticity to adapt to a joint environment has been demonstrated (Kafienah et al, 2002; Wolf et al, 2008; Mumme et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Serum components thus may be required to support in vitro cultivation of nasoseptal chondrocytes because these cells are relatively close to a blood supply in situ as the outer perichondrium is vascularized. Although we did not explore the use of human serum in place of FBS, it previously has been shown that human serum improved the proliferation and matrix synthesis of chondrocytes compared to FBS . Thus, it is expected that human serum, if available, could yield engineered tissues of equal or superior quality compared to FBS using the scaffold‐free, bioreactor‐based method described here.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the extent of esterification, degradation rate can be varied from 1–2 weeks609, 610 to 4–5 months 611, 612. HYAFF® hydrogels are extremely versatile as shown by their capacity to be fabricated into sheets,613 membranes,614 sponges,615 tubes,612, 616, 617 or fibers618, 619 and their usefulness as scaffolds for wound healing618 and the regeneration of the trachea,613 articular cartilage,619 nasal cartilage,615 respiratory epithelium,614 vasculature,612, 616 and nerve tissue 617. Other HA tissue engineering devices include injectables such as SYNVISC ONE® (Genzyme) and ORTHOVISC® (Johnson & Johnson), which have been developed to be injected into the knee to relieve pain from osteoarthritis and improve joint mobility.…”
Section: Enzymatically Degradable Polymersmentioning
confidence: 99%